Analisis Transformasi Digital dalam Pendidikan dan Implikasinya Terhadap Masa Depan - Dorlince O Hutapea; Daniel David Sidebang; Riski Sakti Lumban Gaol; Sri Yunita (Lembaga Pengembangan Kinerja Dosen, 2024)
Digital transformation in education has become a significant phenomenon in the era of disruption. This research discusses the challenges and opportunities that digital transformation in the disruption era provides for education. The results show that digital transformation can help improve the quality of education by utilizing digital technology in the learning process. In addition, digital transformation also helps improve the accessibility of education, facilitate the teaching and learning process, and improve the overall quality of education. In the future, digital transformation is expected to continue to increase the role of technology in education. Teachers and students must continue to adapt to technological developments and utilize technology to improve the quality of education. In synthesis, digital transformation in education has great potential in improving the quality of education and preparing students for a better future.